Arc-Induced Long Period Gratings in Erbium-Doped Fiber - Flavio Esposito; Stefania Campopiano; Agostino Iadicicco (IEEE Photonics Journal)
In this paper, we report about the fabrication of long period gratings (LPGs) directly into an Erbium-doped fiber, by using the electric arc discharge technique. The attention is focused on the writing process and the resulting properties, by considering gratings with different periods and measuring their spectra over a wide wavelength range. The LPGs show high order attenuation bands with tunable resonance wavelengths and depths up to 30 dB, while the lengths of the final devices are in range 20–45 mm. The polarization-dependent loss of these LPGs is also measured, for the first time in this kind of fiber. As further novelty, the influence of surrounding refractive index, applied strain, and temperature is investigated and discussed in comparative manner. Based on the achieved results, this fabrication procedure can be adapted to a specific application, for example in optical communications, signal processing, and sensing fields.